Adsorption isotherm models: A comprehensive and systematic review (2010−2020) - Mozaffari Majd, Mahdieh; Kordzadeh-Kermani, Vahid; Ghalandari, Vahab; Askari, Anis; Sillanpää, Mika (The Science of the total environment, 2022)
Among numerous methods developed in purification and separation industries, the adsorption process has received considerable attention due to its inexpensive, facile, and eco-friendly nature. The importance of the adsorption process causes extraordinary endeavors for modeling the adsorption isotherms during the years; thus, myriads of research have been conducted and many reviews have been published. In this paper, we have attempted to gather the most widely used adsorption isotherms and their related definitions, along with examples of correlated work of the recent decade. In the present review, 37 adsorption isotherms with about 400 references have been collected from the research published in the period of 2010–2020. The adsorption isotherms utilized are alphabetically organized for ease of access. The parameters of each isotherm, as well as the applicable definitions, are presented in the table, in addition to being discussed in the text. Another table is provided for the practical use of researchers, featuring the usage of the related isotherms in peer-reviewed studies. [Display omitted] •The most widely used adsorption isotherm models are reviewed.•The applicable definition and parameters of isotherms are organized in the table.•Numerous practical examples of isotherms used in peer-reviewed studies are presented.